Orientation and long-distance migration routes: an attempt to evaluate compass cue limitations and required precision - Sandberg, Roland; Holmquist, Björn (Wiley-Blackwell, 1998)
By computers imulationso f differentf lightr outesf or springm igratingK nots Calidris canutusp, otentialo rientationa'ld angerz ones' werer evealedi n the equatora rea and northo f the Arcticc ircle.A n evaluationo f the availabilityo f directionailn formation duringm igratoryf lightsd emonstratedth e potentialh azardso f crossingt hese danger zones. Investigationso f the directionalc onsequenceso f sun compass orientation based upon an internalc lock in phase with local time at the departures ite showed that such a mechanism would entail serious losses in distance and time. A simple compensatingr uleb asedo n the rateo f changei n sun altitudew as foundt o workw ell both at polar latitudes and in the equator area. The magnetic compass will become inoperativec lose to the magnetice quatora nd the poles, thus restrictingth e availability of directional information. Orientation by stellar cues will become impossible during spring and summer at arctic latitudes. Simulations of potential migratory routesa lso enablede xaminationo f the requiredp recisiono f compasss ystemsa nd it was indicatedt hat necessaryo rientationa ccuracyr equiresm ore than one directional selectionp er long-distancef light to ensure survival.I t is concludedt hat computer simulations of flight tracks, based on ringing recoveries, visual observations, radar studies and satellite telemetry may be a powerful tool helping to identify problems which require future experimental attention.